Hookworm infection: A neglected tropical disease of mankind - Hossain, Muhammed; Bhuiyan, Jamal Uddin (Journal of Advanced Veterinary and Animal Research, 2017)
Hookworm infection, a global problem of human, is caused by both Ancylostoma duodenale and Necator americanus. These parasites are considered as important blood feeding nematodes. Hookworm is usually prevalent among the people who live with low socio-economic status. However, this tropical disease is neglected in most cases. This review was aimed at investigating the insights of hookworm infection of human considering its epidemiology, pathogenesis, clinical manifestation, diagnosis, treatment, immune mechanism, prevention, and control. This study showed how hookworm infection poses a global burden and infects 438.9 million people around the word annualy, and causes significant morbidity among the children and adult in endemic countries. Also, this review discussed how hookworm infection threatens the mankind causing serious health hazards. http://doi.org/10.5455/javar.2016.c173